2006
DOI: 10.1038/sj.onc.1209836
|View full text |Cite
|
Sign up to set email alerts
|

Silencing expression of UO-44 (CUZD1) using small interfering RNA sensitizes human ovarian cancer cells to cisplatin in vitro

Abstract: Ovarian cancer is currently the second leading cause of gynecological malignancy and cisplatin or cisplatin-based regimens have been the standard of care for the treatment of advance epithelial ovarian cancers. However, the efficacy of cisplatin treatment is often limited by the development of drug resistance either through the inhibition of apoptotic genes or activation of antiapoptotic genes. We have previously reported the overexpression of human UO-44 (HuUO-44) in ovarian cancers and the HuUO-44 antisera m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…CUZD1, also known as UO-44, is expressed in cancerous ovarian tissue and is considered a novel serological biomarker for ovarian cancer [48]. However, Northern blot analysis revealed two differing human pancreatic UO-44 transcripts [49,50]. To the best of our knowledge, corresponding data regarding CUZD1 expression in the intestine are still lacking [17,51].…”
Section: Identification Of Crd-specific Pancreatic Autoantigensmentioning
confidence: 86%
“…CUZD1, also known as UO-44, is expressed in cancerous ovarian tissue and is considered a novel serological biomarker for ovarian cancer [48]. However, Northern blot analysis revealed two differing human pancreatic UO-44 transcripts [49,50]. To the best of our knowledge, corresponding data regarding CUZD1 expression in the intestine are still lacking [17,51].…”
Section: Identification Of Crd-specific Pancreatic Autoantigensmentioning
confidence: 86%
“…This protein, also known as ERG1, Itmap1, or UO-44, was originally identified in our laboratory as an E-regulated gene in the rodent uterine epithelium and later reported in other tissues [2225]. CUZD1 contains a zona-pellucida (ZP)-like domain and two tandem CUB (Complement subcomponent /C1s, Uegf, Bmp1) motifs (S1A Fig).…”
Section: Introductionmentioning
confidence: 99%
“…This observation has led the authors to postulate that human UO-44 may promote cell growth and facilitate invasion in ovarian cancer. The same group of investigators has shown that cisplatin treatment leads to the downregulation of human UO-44 expression and that silencing of human UO-44 based on sequence-specific siRNAs confers an enhanced sensitivity in cisplatin treatment of human ovarian cancer cells [77]. It also appears that UO-44 in ovarian cancer cells with overexpressed human UO-44 are also resistant to cisplatin [77].…”
Section: Cuzd1: As a Cancer Biomarkermentioning
confidence: 99%